COMPARATIVE SIMULATION TESTINGWITH FUNCTIONAL LOADING OF TWO DENTURE FRAMEWORK MATERIALS - A PILOT STUDY - Bojana Chuchulska; Zlatina Tomova; Angelina Vlahova; Ilian Hristov (Peytchinski Publishing, 2022)
Introduction:Simulation tests may significantly decrease the cost and time needed for planning and production of prosthetic restorations, providing both computer simulation as part of the refinement process and experimental testing. Aim: Comparative simulation testing with functional loading of two denture framework materials. Materials and methods: Upper model cast denture forbilateral edentulous areas posterior to the natural teeth (Kennedy Class I) was produced on the "Frasaco" phantom model. The denture was scanned by a 3D optical laboratory scanner. The 3D model was transformed into an STL-file and was processed with "Cinema 4D" software before the application of the program "SOLIDWORKS" v.2018. Parameters of two materials - metal alloy I-MG EKO (Interdent, Slovenia) and injection molded resin Bio Dentaplast (Bredent, Germany) were applied. Simulations were performed by equivalent loading according to the Third strength theory (von Mises stress-test) and loading with deformation and shift at constant force 0.1N/mm2 at a maximal number of 159 181 segmented elements of the 3D object. Tests were held upon unilateral loading on the working side, and support was provided by reciprocal clasp arms on the working and non-working side, denture flanges and major connector. Results and discussion: Results showed insignificant differences between the common reflected load of the two tested materials but with different distribution - on the major connector, it was 0.4N for the alloy and 0.87N for the resin, at the flanges - 2.26N and 5.6N respectively, for the clasps - 5.1N and 5.7N. Conclusion: The tested metal alloy is rigid and resistant material which provides distribution of the reflected load between clasp elements and denture saddle, especially distally, while the the tested injection molded material possesses relatively high flexibility and elasticity, which hides a risk for the teeth bearing clasps.